The neutrophil recombinatorial TCR-like immune receptor is expressed across the entire human life span but repertoire diversity declines in old age - Fuchs, Tina; Scharfenstein, Olivia; Eichner, Romy; Pechlivanidou, Ioanna; Kzhyshkowska, Julia; Gratchev, Alexei; Neumaier, Michael; Kaminski, Wolfgang E. (Biochemical and biophysical research communications, 2012)
Recent evidence has revealed the existence of T cell receptor (TCR) αβ-based recombinatorial immune receptors in phagocytes. Here, we performed a systematic survey of the variable β-chain repertoires of the neutrophil TCR-like αβ immunoreceptor (referred to as TCRLnαβ) in defined cohorts of young and old individuals. Peripheral blood CD15+ neutrophils from young adults (age 30±7years, n=12) expressed an average number of 13±6 distinct TCRLn Vβ-chains from the total pool of 25 human Vβ-chains. Neutrophils from aged subjects (age 76±6years, n=12) also consitutively express the TCRLn, however, only a small number of Vβ-chains is used (4±2). Consistent with this, the average number of expressed CDR3 Vβ length variants was fourfold higher in young individuals than in aged subjects (33±24 vs. 8±3). Young adults showed broad usage of all TCRLn Vβ-chains. In contrast, >70years individuals displayed a striking repertoire polarization towards the TCRLn Vβ1 and Vβ5b chains and a high degree of Vβ5b clonotype sharing. Our study reveals broad TCRLn repertoire diversity in young adults and demonstrates that the neutrophil variable immune receptor is expressed throughout the entire human life span. The marked decline in TCRLn repertoire diversity in old age identifies a novel mechanism of immunosenescence in neutrophils.